Identifikation des menschlichen Bewegungsverhaltens auf der Basis von Primitiven - Diehm, Gunter (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik / Karlsruher Institut für Technologie, Institut für Regelungs- und Steuerungssysteme, 2017)
The consideration of discrete motor primitives in models of human motor control is essential for the realistic prediction of voluntary movements. In this book a formal movement model is derived from neurobiological findings as well as new identification and learning methods are presented for the secured determination of the model parameters. Both the model and the identification methods are demonstrated using the example of predicting human driver steering movements.